Desain Pit Penambangan Lapisan Batubara Seam C pada Pit X PT. Bukit Asam Tbk. - Nabilla Kansha; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. Based on the Decree of the Minister of Energy and Mineral Resources No. 1827K concerning Guidelines for the Implementation of Good Mining Rules, states that every mining company is required to report a management plan for the remaining reserves in its territory as part of conservation. One of the conservation efforts is to carry out mining of unmined reserves. This can be used to achieve the effectiveness and efficiency of the desired target. This also helps to maintain the availability of coal when certain qualities cannot be met by PT Bukit Asam Tbk. Mining operations basically require design and economic studies to get optimal results. Based on the study that has been carried out, the seam c coal seam in pit 1 north of Banko Barat has the potential to be optimized which produces a coal volume of around 442,769.68 tons with a stripping ratio of 2.9. Based on the study of Break even stripping ratio (BESR), the result is 15.7 with an economical SR of 9.76, it can be concluded that the design that has been designed is feasible to mine because it does not exceed the economical SR.